2019
DOI: 10.1042/bsr20191575
|View full text |Cite
|
Sign up to set email alerts
|

The effect of group B streptococcus on maternal and infants’ prognosis in Guizhou, China

Abstract: Group B Streptococcus (GBS) is a kind of opportunistic pathogenic bacteria and mainly strikes the lower digestive tract and genitourinary tract. It is a major risk factor for neonatal babies, seriously threatening their lives. In the present study, we aimed to detect the GBS colonization in late pregnant women, and to study the effect of GBS on maternal and infants’ prognosis. Pregnant women with a gestational age of 35–37 weeks were enrolled in the study. Real-time polymerase chain-reaction (RT-PCR) was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…(AOR = 3.44, 95% CI = 1.34–8.83, p -value = 0.01). This finding is in line with other similar studies conducted in China [ 55 ], Nigeria [ 56 ], and Ethiopia [ 35 , 48 , 57 ]. According to different reports, GBS infection during pregnancy can cause complications like miscarriage, premature labor, or stillbirth.…”
Section: Resultssupporting
confidence: 93%
“…(AOR = 3.44, 95% CI = 1.34–8.83, p -value = 0.01). This finding is in line with other similar studies conducted in China [ 55 ], Nigeria [ 56 ], and Ethiopia [ 35 , 48 , 57 ]. According to different reports, GBS infection during pregnancy can cause complications like miscarriage, premature labor, or stillbirth.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, the rapid and accurate screening of GBS is essential, which is closely related to methodology. In this study the colonization rate was found to be 10.1% that was consistent with the previous reports of 3.7-14.5% in China (Dai et al, 2019;Huang et al, 2019), which was close to Korea (11.6%) (Kim et al, 2018), slightly higher than that in India (7.6%) (Santhanam et al, 2017), but much lower than that in America (21.6%) (Edwards et al, 2019). In addition to geography, ethnicity, socioeconomics, health, and nutritional factors, prevalence of GBS colonization in pregnant women is also influenced by sampling and screening methodologies.…”
Section: Discussionsupporting
confidence: 92%
“…Wei et al. ( Dai et al., 2019 ) conducted research on 380 women in late pregnancy and found that the puerperium infection was related to the colonization of GBS (AV pathogen) during pregnancy. The presence of pathogen of VVC and GBS simultaneously may increase the risk of puerperium infection.…”
Section: Discussionmentioning
confidence: 99%